Áoikoi gunaîkes en Sófocles - Morenilla, Carmen (Palabras sabias de mujeres: teatro y sociedad en la antigüedad clásica, 2013)
In this paper we study first how Antigone and Electra act and second how Deianeira, Eurydice and Jocasta act. Antigone and Electra do not hold their own "oikos" and none of them take a part into their father "oikos". As they have to fulfil an obligation wíth their deceased relatives, they were compelled to reject the new lord of the "oikos". Both of them elaborate the justification of the decision they have been taken because they have proceeded in a different way that woman behaviour is expected. However, the "oikos" of Deianeira, Eurydice and Jocasta had been destroyed so they miss everything concerned to the sphere of action of the Greek woman. They can only enter at the house in silence and die.